'Along Kingdom's Highway': the proliferation of Christianity, education, and print amongst the Nagas in Northeast India. Issue 2 (3rd April 2019) - Longkumer, Arkotong
Abstract : The aim of this paper is to examine the story of the American Baptists and how their mission activities in the Naga Hills District (1871–1955) have impacted upon present day politics in the Indian state of Nagaland. Baptists make up nearly 95% of the current Naga population in Nagaland. The paper will investigate the relationship between the Baptist mission's philosophy on education, Christian conversion and the subsequent rise of a sense of 'national community' amongst the Nagas. Although the primary motivation for the American missionaries was to convert, the British administrators also thought that introducing Christianity would prevent influence on these tribes from Hindu and Muslim groups. Thus began Christianity's part in a developing framework for resistance in this region, raising significant questions with regard to Christianity's persistence as a form of political articulation in contemporary Nagaland. This political articulation, I suggest, is related to a greater sense of agency brought about by Christianity and Missionary activities in the fields of education and print. The American Baptist Foreign Mission Society (ABFMS) was at the forefront of these changes.